Biological effects of ultrashort electric pulses in a neuroblastoma cell line: the energy density role. (2nd January 2022) - Consales, Claudia; Merla, Caterina; Benassi, Barbara; Garcia-Sanchez, Tomás; Muscat, Adeline; André, Franck M.; Marino, Carmela; Mir, Lluis M.
Abstract: Background: Despite the numerous literature results about biological effects of electromagnetic field (EMF) exposure, the interaction mechanisms of these fields with organisms are still a matter of debate. Extremely low frequency (ELF) MFs can modulate redox homeostasis and we showed that 24 h exposure to 50 Hz–1 mT has a pro-oxidant effect and effects on the epigenome of SH-SY5Y cells, decreasing miR-34b/c expression through the hypermethylation of their promoter. Methods: Here, we investigated the role of the electromagnetic deposited energy density (ED) during exposures lasting 24 h to 1 mT amplitude MFs at a frequency of 50 Hz in inducing the above mentioned effects. To this end, we delivered ultrashort electric pulses, in the range of microsecond and nanosecond duration, with the same ED of the previously performed magnetic exposure to SH-SY5Y cells. Furthermore, we explored the effect of higher deposited energy densities. Analysis of i) gene and microRNA expression, ii) cell morphology, iii) reactive oxygen species (ROS) generation, and iv) apoptosis were carried out. Results: We observed significant changes in egr-1 and c-fos expression at very low deposited ED levels, but no change of the ROS production, miR-34b/c expression, nor the appearance of indicators of apoptosis. We thus sought investigating changes in egr-1 and c-fos expression caused by ultrashort electric pulses at increasing deposited ED levels. The pulses with the higher deposited ED caused cell electroporation and even other morphological changes such as cell fusion. The changes in egr-1 and c-fos expression were more intense, but, again, no change of the ROS production, miR-34b/c expression, nor apoptosis induction was observed. Conclusions: These results, showing that extremely low levels of electric stimulation (never investigated until now) can cause transcriptional changes, also reveal the safety of the electroporating pulses used in biomedical applications and open up the possibility to further therapeutic applications of this technology.